Autoimmune Disease with Cardiac Valves Involvement: Libman-Sacks Endocarditis - Eka Ginanjar; Yulianto Yulianto (Interna Publishing, 2017)
This case study aim to evaluate the response of steroid treatment for autoimmune endocarditis. Valvular heart disease is relatively rising in both congenital and acquired cases, but the autoimmune endocarditis remains rare. In this case, a 34 year old woman with clinical manifestation resembling systemic lupus erythematosus (SLE) is diagnosed with Libman-sacks Endocarditis. After six months of steroid treatment, her clinical manifestations and heart structure improved.